A Comparative Study of Fair Online Buying and Selling Regulations: A Legal Comparison Between Indonesia, Malaysia, and Singapore - Rahman, Muhammad Sabir (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The practice of buying and selling online is part of the development of digitalization and technology. Regulation of fair online buying and selling practices by the state is important to protect the rights of the parties.Purpose of the Research: This research aims to analyze and compare online buying and selling arrangements implemented in Indonesia, Malaysia and Singapore.Method of Research: Normative legal research by prioritizing conceptual, statutory and conceptual approaches.Results of Research: Regulation of online buying and selling in Indonesia is viewed from the aspect of distributive justice because the practice of equal playing field, namely equalizing business actors from abroad and from within the country, has not been accompanied by empowerment efforts and special treatment for small, micro and medium businesses in Indonesia, despite its commutative justice aspect, has accommodated various efforts to protect sellers and buyers in online buying and selling transactions. Comparison of the legal regulations for online buying and selling between Indonesia and Malaysia and Singapore. In general, Malaysia and Singapore have provided special arrangements and appropriate and fast procedures regarding means of complaints and the process for complaints in online buying and selling transactions is carried out comprehensively to ensure that everyone or parties involved in online buying and selling transactions have their complaints heard and followed up. Therefore, Indonesia needs to improve regulations related to online buying and selling transactions, especially regarding optimizing complaint services as implemented in Malaysia and Singapore, which follow up on complaint services within a certain period of time and are processed to provide legal certainty and protection for the parties involved in the transaction. online buying and selling transactions.